If p(x) = x-1, then the value of p(1) + p(-1)is?
Answers
Answered by
2
Step-by-step explanation:
this is the correct answer
Attachments:
![](https://hi-static.z-dn.net/files/d25/8c6208123547657a86966c796079939d.jpg)
Answered by
0
Answer:
If p(x) = x-1, then the value of p(1) + p(-1) is: -2
Step-by-step explanation:
- Given: p(x)= x-1
- To find: p(1)+p(-1)
- Here given function of p is x and we have to find the function of p of p(1)+p(-1).
- Then the value of p(x)=x-1,
- So substituting the value of x as 1 and -1.
- Therefore p(1)= 1-1=0
- And p(-1)=-1-1= -2
- Now substituting the value of p(1) and p(-1) will be:
- p(1)+ p(-1)= 0+(-2)
- p(1)+p(-1)= -2
Hence the value of, p(x) = x-1, then the value of p(1) + p(-1) is -2
Similar questions